Lessons from the Titans - Davis, Scott; Copeland, Carter; Wertheimer, Rob (McGraw Hill-Ascent Audio, 2021)
Before Silicon Valley disrupted the world with new technologies and business models, America's industrial giants paved the way. Companies like General Electric, United Technologies, and Caterpillar were the Google and Amazon of their day, setting gold standards in innovation, growth, and profitability. Today's leaders can learn a great deal from their successes, as well as their missteps. In this essential guide, three veteran Wall Street analysts reveal timeless lessons from the titans of industry-and offer battle-tested survival tactics for an ever-changing world. You'll learn: how GE became the largest company on earth-only for a culture of arrogance to set in motion the largest collapse in history; how Boeing reassessed risks, raised profits-and tragically lost its balance; how Danaher avoided the pitfalls of tremendous success-by continually reinventing itself; how Honeywell experienced a near-fatal cultural breakdown-and executed a flawless turnaround; and how Caterpillar relied too much on forecasting, lost billions-and rallied by recommitting to the basics. Filled with illuminating case studies and brilliant in-depth analysis, this invaluable book provides a multitude of insights that will help you weather market upheavals, adapt to disruptions, and optimize your resources to your best advantage.
Online resource; Title from title page (viewed June 29, 2021)
Keywords: Audiobooks; Livres audio